In vivo vascularization of cell sheets provided better long‐term tissue survival than injection of cell suspension. (28th January 2014) - Takeuchi, Ryohei; Kuruma, Yosuke; Sekine, Hidekazu; Dobashi, Izumi; Yamato, Masayuki; Umezu, Mitsuo; Shimizu, Tatsuya; Okano, Teruo
Abstract: Cell sheets have shown a remarkable ability for repairing damaged myocardium in clinical and preclinical studies. Although they demonstrate a high degree of viability as engrafted cells in vivo, the reason behind their survivability is unclear. In this study, the survival and vascularization of rat cardiac cell sheets transplanted in the subcutaneous tissue of athymic rats were investigated temporally. The cell sheets showed significantly higher survival than cell suspensions for up to 12 months, using an in vivo bioluminescence imaging system to detect luciferase‐positive transplanted cells. Terminal deoxynucleotidyl transferase dUTP nick‐end labelling (TUNEL) assay also showed a smaller number of apoptotic cells in the cell sheets than in the cell suspensions at 1 day. Rapid vascular formation and maturation were observed inside the cell sheets using an in vivo imaging system. Leaky vessels appeared at 6 h, red blood cells flowing through functional vessels appeared at 12 h, and morphologically matured vessels appeared at 7 days. In addition, immunostaining of cell sheets with nerve/glial antigen‐2 (NG2) showed that vessel maturity increased over time. Interestingly, these results correlated with the dynamics of cell sheet mRNA expression. Genes related to endothelial cells (ECs) proliferation, migration and vessel sprouting were highly expressed within 1 day, and genes related to pericyte recruitment and vessel maturation were highly expressed at 3 days or later. This suggested that the cell sheets could secrete appropriate angiogenic factors in a timely way after transplantation, and this ability might be a key reason for their high survival. Copyright © 2014 John Wiley & Sons, Ltd.